The moderating effect of channel use on the quality-loyalty relationship in multi-channel e-services - Sousa, Rui (2013)
Purpose – Services provided through the internet (e-services) are typically offered as part of a broader Multi-Channel (MC) service package, combining these services with services delivered through traditional channels (e.g. phone, physical facilities). Customers of e-services display heterogeneity in channel use, ranging from customers with a high Degree of Focus on the Internet (DFI) channel (internet-oriented customers) to customers with a low DFI (low focus on the internet and strong reliance on traditional channels). The purpose of this study is to examine whether a customer’s DFI moderates the relationship between e-service quality (eSQ) and e-loyalty behavioral intentions in an MC e-service. Design/methodology/approach – Perceptual and objective data were collected from multiple sources in a major retail MC e-banking service (survey of online customers, transactional data and customer database). Findings – First, there is high diversity in DFI among e-service customers; second, a customer’s DFI negatively moderates the quality-loyalty relationship. Research limitations/implications – The study should be extended to other types of e-services. Practical implications – eSQ seems to be a more important driver of e-loyalty behavioral intentions for low DFI customers than for high DFI (internet-oriented) customers. Different strategies may need to be employed to drive retention across customers with different levels of DFI. Specifically, driving e-loyalty among internet-oriented customers may require complementing eSQ investments with additional retention mechanisms (e.g. building communities or creating switching barriers). DFI should be recognized as a useful and readily available customer segmentation variable for devising loyalty strategies. Originality/value – The study pioneers the examination of the impact of channel use on the quality-loyalty relationship. It breaks new ground in proposing DFI as a relevant customer segmentation variable for e-service research and practice. External validity is enhanced by the use of objective (rather than self-reported), real-world data to measure customer channel use.